Seroprevalence of COVID-19 antibodies in the cleaning and oncological staff of a municipal clinic - Epstude, Jörg; Harsch, Igor Alexander (German Medical Science GMS Publishing House, 2020)
Aim: To prevent shedding of the novel COVID-19 virus in hospitals, strict hygiene measures and surveillance of the staff and patients is mandatory. Studying the available literature, we assumed that monitoring of the cleaning staff may sometimes be a "blind spot" in surveillance. Although the cleaning personnel is not entrusted with the medical and nursing care of patients, the extent of patient contacts in this group may be comparable to medical personnel and even increase in times of a visit ban in many hospitals. The aim of this study was to investigate the prevalence of COVID-19 infections already undergone in this group. Methods: Antibody titers (IgA and IgG) against COVID-19 were measured in the cleaning staff from June 15 to 30, 2020 in our clinic. Antibodies against COVID-19 were determined using ELISA (, PerkinElmer, Inc. Company). For purposes of comparison, the same procedure was performed in the staff of the oncology ward, who were regarded as an important group due to their high-risk patients.Results: During the study period, 45 members of the cleaning staff and 20 members of the oncology ward were tested. Significantly elevated IgA antibody titers were detected in 1 person in the first group and in 1 person in the second group. Significantly elevated IgG antibody titers were not detected in the first group and in 1 person of the second group. In case of positive or indeterminate testing, swabs for direct virus detection were taken, but were negative in all cases.Conclusion: The prevalence of already undergone infections in both groups is low, as to be expected due to the still low incidence of COVID-19 infections in the German federal state of Thuringia. However, the presence of such antibodies in the cleaning personnel demonstrates the need for equally strict surveillance in this group.